The Influence of Company Size on Risk Management Disclosure With Good Corporate Governance as a Moderation Variable in the Company Listed Property and Real Estate on the Indonesian Stock Exchange (IDX) - Benny Pasaribu; Rahima Br Purba; Renny Maisyarah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine how firm size affects risk management disclosure in property and real estate companies listed on the Indonesia Stock Exchange, using Good Corporate Governance (GCG) as a moderating factor. In this study, company size is the independent variable, risk management disclosure is the dependent variable, and GCG serves as a moderating variable. Associative, quantitative research methodology is employed, and linear analysis techniques are applied for analysis. Using a purposive sample approach, the study's population consists of property and real estate companies listed between 2018-2021 on the Indonesia Stock Exchange. The study's findings indicate that risk management disclosure is significantly impacted by a company's size. Nevertheless, in the context of property and real estate businesses listed on the Indonesia Stock Exchange for the examined period, GCG was not demonstrated to be able to control the relationship between company size and risk management disclosure